Bionic Ears: Their Development and Future Advances Using Neurotrophins and Inherently Conducting Polymers - Graeme M. Clark; Gordon Wallace (Applied Bionics and Biomechanics)
The development of the multiple-channel bionic ear for hearing and speech understanding in profoundly deaf people is the result of integrating biological and physical sciences with engineering. It is the first clinically successful restoration of sensory and brain function, and brings electronic technology into a direct functional relationship with human consciousness. It presently transmits essential place and coarse temporal information for the coding of frequency, but the fine temporal and place excitation of groups of nerve fibres is inadequate for high-fidelity sound. This is required for adequate musical appreciation and hearing in noise. Research has demonstrated that nerve growth factors preserve the peripheral processes of the auditory nerves so that an electrode array placed close to these fibres could produce this fine temporal and spatial coding. The nerve growth factors can be incorporated into inherently conducting polymers that are part of the array so the peripheral processes can be preserved at the same time as they are electrically stimulated.